PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL, KOMPLEKSITAS OPERASI, DAN LEVERAGE TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Konsumsi Yang Terdaftar Di Bursa Efek In - EMIL LIA MAJID (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of profitability, firm size, managerial ownership, operating complexity, and leverage on the timeliness of financial statement submission. Empirical study on consumption industry companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling method used purposive sampling. The samples obtained in this study were 81 companies that had sample criteria. The results of this study are that profitability as proxied by ROA has no effect on the timeliness of submitting financial reports, Company size affects the timeliness of submitting financial reports, Managerial Ownership proxied by MOWN does not affect the timeliness of submitting financial statements, Operational Complexity proxies by Dummy has no effect on the timeliness of submitting financial statements, and the leverage proxied by DER has no effect on the timeliness of submitting financial statements. Keywords: Profitability, Firm Size, Managerial Ownership, Operational Complexity, Managerial Ownership, Leverage